Profesionalisme Tour Leader dalam Pelayanan Jamaah Umrah Studi Pengalaman Magang Mahasiswa UINSU di PT Amar Madani Masyhur Islamic Tour and Travel - Muhammad Gilang Ramadhan; Abdul Halim; Ranse Wirani; Aulia Permata Sari; Indita Rinanty Br. Damanik; Sholatiah Sholatiah; Muhammad Arif Fadhilah; Annisa Rahma Aulia (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
This study aims to analyze the internship experience of UINSU students at PT Amar Madani Masyhur Islamic Tour and Travel in the context of professionalism in serving Umrah pilgrims by tour leaders. The analysis focuses on four main aspects: the company’s profile and history, tour leader service management, forms of services provided, and the effectiveness of services in enhancing pilgrims’ satisfaction. Tour leader professionalism plays a crucial role in ensuring a smooth spiritual journey through responsive, structured, and integrity-based assistance. The research employs a qualitative-descriptive method with a field study and participatory observation approach, including interviews, documentation, and service evaluation during the internship program. The findings indicate that PT Amar Madani Masyhur implements a well-organized tour leader management system, covering administrative services, manasik guidance, ritual assistance, as well as accommodation and transportation services that effectively meet pilgrims’ needs. The novelty of this study lies in integrating institutional profile analysis with students’ practical experiences in understanding professional standards of competent, integrity-driven, and service-oriented tour leaders.